ISLAMIC RELIGIOUS EDUCATION TEACHER STRATEGIES IN INFLUENCED ISLAMIC VALUES THROUGH FIQH MATERIALS IN STUDENTS OF SDIT MIFTAHUL ULUM SUBANG - Hasan, Muhammad Zaki Akhbar; Khairunnida, Laila; Parid, Miptah; Amaliya, N. Fitri; Mohamed Shendi, Hebaallah Ahmed Abdel Halim (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
The background of this research is the important role of Islamic religious education teachers in instilling Islamic values to students, especially through the learning of Fiqh material at SDIT Miftahul Ulum Subang. In elementary education, Islamic religious education teachers play a strategic role in shaping the religious character of students so that they are able to understand, appreciate, and practice Islamic teachings comprehensively. The purpose of this research is to describe the strategies of Islamic religious education teachers in instilling Islamic values through Fiqh material and to analyze the effectiveness of implementing these strategies on the formation of student character. This research method uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation which were then analyzed interactively through data reduction, data presentation, and drawing conclusions. The results show that Islamic religious education teachers at SDIT Miftahul Ulum Subang apply an integrative learning strategy by combining lectures, discussions, role models, and habits in school religious activities. This strategy has proven effective in fostering Islamic values such as religious discipline, honesty, responsibility, and social awareness among students. In conclusion, the Islamic religious education teachers' strategy in instilling Islamic values through Fiqh (Islamic jurisprudence) material at SDIT Miftahul Ulum Subang is effective and sustainable. Teachers act as educators and role models, integrating Islamic values through role models, fostering worship practices, and reflecting on values in learning.